Management models of tourism industry: The case of Greece - Papadopoulou, Georgia (Open Science Journal, 2020)
Management has been the focus of studies in the field of tourism and hospitality and other related sectors. However, recently, investigators began examining the role of a management model in improving the competitiveness of a country both at the firm and state level. The literature reviewed in the current study has shown that management models affect the success, productivity, and effectiveness of firms in the sector. More researchers have noted that the management model should focus on the sustainability of the ecosystem and economy. The management model adopted by Greece has not been effective in improving its level of competitiveness compared to other European nations. Although various studies have examined the phenomenon, there is yet a need for more explorations to exploit how various antecedents of management models affect the tourism sector in the long-run. The current study has established that the management model supported by positive government policies affects the tourism industry and attracts more visitors, growth, and competitiveness.